Effect of pruning on the Capsicum annum L. yield under two environments - Orozco-Orozco, Luz Fanny; Lozano-Fernandez, Jaime (Agronomía Mesoamericana, 2021)
Introduction. Pruning the stems of bell pepper has been recommended to improve light interception, increase fruit set, and the quality of fruits. Objective. To evaluate the effect of pruning on yield components of two pepper hybrids established in two environments: open field and protected field under roof with plastic and natural ventilation. Materials and methods. Two trials were conducted at the La Selva Research Center of the Corporación Colombiana de Investigación Agropecuaria (AGROSAVIA), Rionegro, Antioquia, Colombia. Two pepper hybrids of block type were evaluated in two environments: open field (in the 2013-2014 cycle) and protected field under plastic cover (in the 2013-2014, 2014-2015 cycles), and three formation pruning treatments: two stems, three stems, and no pruning. For the first experiment, a randomized complete block design with six treatments (two hybrids and three pruning systems) and five replicates was used. For the second, the same treatments were established only under the protected environment, in a randomized complete block design. Results. Statistical differences were found for total yield in the unpruned system in both trials. In the protected field–2013 the hybrids achieved an average yield of 36.7 t ha-1, the unpruned system was the highest yielding (49.7 t ha-1). In the open field the yield was 23.6 t ha-1. The total yields obtained under the protected field-2014 (36.2 t ha-1), equaled that obtained in 2013, and statistically exceeded those of the open field. Conclusion. Unpruned plants showed the best yields in both trials. Differences between environments, hybrids, and their interaction were present in some variables. Further studies should be carried out to determine if the protected environment is suitable for the development of the hybrids.